2019
DOI: 10.3390/ijerph16234853
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training Load on Post-Exercise Cardiac Troponin T Elevations in Young Soccer Players

Abstract: Training load (TL) metrics are usually assessed to estimate the individual, physiological and psychological, acute, and adaptive responses to training. Cardiac troponins (cTn) reflect myocardial damage and are routinely analyzed for the clinical diagnosis of myocardial injury. The association between TL and post-exercise cTn elevations is scarcely investigated in young athletes, especially after playing common team sports such as soccer. The objective of this study was to assess the relationship between TL mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 40 publications
4
26
1
Order By: Relevance
“…A higher and more variable release of the biomarker during puberty might explain why some differences were found in adolescent-adult comparisons but not in children-adult studies. This hypothesis goes in line with our recent study in which we found that in a cohort of 20 participants of 11.9 ± 2 years, the elevation of cTnT after exercise was positively associated with the maturational stage of participants obtained using a Tanner scale [10]. In this regard, previous authors have already highlighted the need for age-and sex-specific population values for cTnT concentrations in pediatrics [25].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…A higher and more variable release of the biomarker during puberty might explain why some differences were found in adolescent-adult comparisons but not in children-adult studies. This hypothesis goes in line with our recent study in which we found that in a cohort of 20 participants of 11.9 ± 2 years, the elevation of cTnT after exercise was positively associated with the maturational stage of participants obtained using a Tanner scale [10]. In this regard, previous authors have already highlighted the need for age-and sex-specific population values for cTnT concentrations in pediatrics [25].…”
Section: Discussionsupporting
confidence: 89%
“…Exercise load has previously been correlated with ∆cTnT [8,10]. Similarly, players in this study who covered larger distances, ran at a higher speed, or performed at higher HR were those who presented a higher ∆cTnT ( Table 3).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations